2014
DOI: 10.1093/nar/gku861
|View full text |Cite
|
Sign up to set email alerts
|

Nova1 is a master regulator of alternative splicing in pancreatic beta cells

Abstract: Alternative splicing (AS) is a fundamental mechanism for the regulation of gene expression. It affects more than 90% of human genes but its role in the regulation of pancreatic beta cells, the producers of insulin, remains unknown. Our recently published data indicated that the ‘neuron-specific’ Nova1 splicing factor is expressed in pancreatic beta cells. We have presently coupled specific knockdown (KD) of Nova1 with RNA-sequencing to determine all splice variants and downstream pathways regulated by this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 81 publications
(119 reference statements)
6
80
2
Order By: Relevance
“…We have previously shown that Nova1 controls beta cell function and survival by regulating genes involved in exocytosis, apoptosis, insulin receptor signaling, splicing, and transcription (27). Here we provide additional data showing that Nova2 depletion impairs beta cell survival but not insulin secretion.…”
Section: Role Of Neuron-enriched Rna-binding Proteins In Beta Cellssupporting
confidence: 58%
See 2 more Smart Citations
“…We have previously shown that Nova1 controls beta cell function and survival by regulating genes involved in exocytosis, apoptosis, insulin receptor signaling, splicing, and transcription (27). Here we provide additional data showing that Nova2 depletion impairs beta cell survival but not insulin secretion.…”
Section: Role Of Neuron-enriched Rna-binding Proteins In Beta Cellssupporting
confidence: 58%
“…Here we provide additional data showing that Nova2 depletion impairs beta cell survival but not insulin secretion. Increased apoptosis by Nova2 KD may be secondary to up-regulation of the FoxO3A transcription factor and pro-apoptotic protein Bim, as observed previously in Nova1 KD (27). The absence of insulin secretion defects may be explained by differences in targets genes between the Nova paralogs.…”
Section: Role Of Neuron-enriched Rna-binding Proteins In Beta Cellssupporting
confidence: 54%
See 1 more Smart Citation
“…To further investigate the role of individual splicing factors in the regulation of β cell function and survival, we studied the ‘neuron-specific’ RBP NOVA1 using siRNA silencing coupled with RNA-seq (12) (Fig. 5).…”
Section: β Cell Death In Type 1 Diabetes and The Role Of Asmentioning
confidence: 99%
“…These splicing regulators are RNA-binding proteins (RBPs) of the serine/arginine (SR)-rich proteins and heterogeneous nuclear RNPs (hnRNP) families, as well as other cell-, stage- or tissue-specific proteins such as the NOVA, RBFOX, CELF or MBLN families. These families establish the splicing code and determine in a combinatorial fashion which splice site is selected in specific tissues (for instance, NOVA1 is only expressed in brain and pancreatic β cells) (11, 12, 13, 14). The regulation of AS is accomplished by the relative expression levels of the different RBPs, determining how efficiently different splice sites are used to generate specific mRNA isoforms in different cells and tissues.…”
Section: Introductionmentioning
confidence: 99%